Effect of Tempol on the prevention of irradiation‐induced mucositis in miniature pigs. (27th April 2017) - Hu, L; Wang, Y; Cotrim, AP; Zhu, Z; Gao, R; Zheng, C; Goldsmith, CM; Jin, L; Zhang, C; Mitchell, JB; Baum, BJ; Wang, S
Abstract : Objective: The goals of this study were to (i) establish a useful miniature pig (minipig) model for irradiation‐induced oral mucositis and (ii) evaluate the effect of Tempol to prevent its development. Methods and Materials: Minipigs were irradiated with 6 Gy for five consecutive days targeting the entire oral cavity. To prevent radiation damage, minipigs were treated with 30 mg kg −1 Tempol 10 min before irradiation ( n = 4), while the radiation‐alone group was similarly injected with saline ( n = 4). Lesions were graded using an oral mucositis score and visual inspection every 3 days, and biopsy of multiple sites was performed at day 18. Weight and chest and abdominal circumferences were measured every 3 days. Results: Lesions began about 12 days after the first irradiation fraction and healed about 30 days after irradiation. Epithelial thickness was calculated on the lingual and buccal mucosa on the 18th day after the first irradiation fraction. Tempol provided modest protection from ulceration after irradiation using this treatment strategy. Conclusions: This study established a useful large animal model for irradiation‐induced oral mucositis and showed modest beneficial effects of Tempol in limiting tissue damage. The latter finding may be potentially valuable in preventing oral mucositis in patients receiving irradiation for head and neck cancers.